Innovation activities in aquatic processing enterprises in Khanh Hoa province - Kieu Chau, Huynh Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
During more than 10 last years, aquatic processing sector in Khanh Hoa Province has passed a clear shift in development. The traditional economic sector has shifted to market driven economy and catching- up with integration trends contributing to efforts to turn it to a leading economic sector of the province. However, in order to enhance technological capacities of enterprises then to make them the platform for developing competitiveness it is necessary to have innovations and management of innovations in these enterprises. This paper reflects main features of the shift and factors for activities of innovations of aquatic processing enterprises. This would help administrators to keep practical insights for supporting these enterprises during their development process. At the same time the enterprises would note their week points when setting up plans and strategies for future stable development. Code: 13022101